Global research landscape and emerging trends of non-coding RNAs in prostate cancer: a bibliometric analysis - Zhou, Yu-Liang; Yao, Wen-Liang; Chen, Sheng-Hui; Wang, Peng; Fu, Jing-Wen; Zhao, Jia-Qin; Zhang, Jia-Yi (Frontiers in Pharmacology, 2025)
BackgroundProstate cancer (PC) is the most frequently diagnosed cancer in men and continues to be a major cause of cancer-related mortality worldwide. In recent years, non-coding RNAs (ncRNAs) have emerged as a significant focus in molecular biology research, playing a pivotal role in the development and progression of PC. This study employed bibliometric analysis to explore the global outputs, research hotspots, and future trends in ncRNA-related PC research over the past 20 years.MethodsPublications on PC-related ncRNAs from 2004 to 2023 were retrieved from Web of Science Core Collection. The co-operation network of countries, institutions, and authors on this topic was analyzed using CiteSpace (version 6.2. R6). In addition, co-occurrence analysis of keywords and co-citation analysis of references were performed using CiteSpace, and emergent detection was also performed.ResultsA total of 2,951 articles on PC-related ncRNAs were finally included in this study for analysis. China contributed the largest number of publications, while the United States was the most influential country in this field, with collaborative ties to 26 other countries. Fudan University was identified as the most active institution in this field. Rajvir Dahiya was the most prolific and influential author. Within the co-citation network, clusters labeled “EVs,” “circRNA,” and “ceRNA” represented current research directions. The cluster labeled “gene” dominated the co-occurrence keywords. “circRNA” showed the highest burst strength among keywords, with “circRNA,” “EVs” and “exosome” maintaining sustained burst strength, suggesting these are the emerging research frontiers in this field.ConclusionInvestigating ncRNAs as pivotal research subjects in PC is essential for addressing the public health impact of the disease and advancing innovative diagnostic and targeted therapeutic strategies. This study provides a comprehensive bibliometric analysis of research related to PC-associated ncRNAs, delivering a scientific perspective and identifying potential research directions for scholars in this field.